Introduction to Buddhist East Asia - Scott, Robert H.; McRae, James (SUNY series in Asian studies development, 2023)
Offers a variety of pedagogical and theoretical essays designed to assist professors in introducing undergraduate students to Buddhism in China, Korea, and Japan.